The School for Social Innovation at Huguenot College and congregational vitality through faithful innovation - C.J.P. Niemandt (Acta Theologica)
This article presents a case study and the story of the School for Social Innovation (SSI) at Hugenote Kollege in Wellington, South Africa. It explores the influence of Andrew Murray Jr, the history of the college, the relationship between the college and the Dutch Reformed church in South Africa, and the establishment of the School for Social Innovation (SSI). It explores the concept of “social innovation”. The research provides a brief overview of SSI programmes, the short courses presented for church and community leadership on the theme of social innovation, and the social awareness programme known as #Integritas. The article also explores the interface and mutual insights between social innovation and faithful  innovation and proposes ways in which the narrative of the SSI might enrich discourses on congregational vitality. These explorations might unearth theories, practices, and approaches to leadership that engage with Schoeman’s work and broaden the understanding of congregational vitality through faithful innovation.